A rare case mimicking positron emission tomography/computed tomography mismatch: Hepatic subcapsular hematoma - TÜNEY, DAVUT; İNANIR, SABAHAT (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Subcapsular collections of bile, air or blood in the liver have been described following transhepatic procedures due to the leakage of bile and blood from the percutaneous puncture at the surface of the liver. Herein we presented the subcapsular collection led to a mismatch between functional and anatomical boundaries of the liver.
Keywords: F-18 fluorodeoxyglucose; hematoma; liver; positron emission tomography/computed tomography; subcapsular collection